Identification and Immunogenicity of African Swine Fever Virus Antigens - Netherton, Christopher L.; Goatley, Lynnette C.; Reis, Ana Luisa; Portugal, Raquel; Nash, Rachel H.; Morgan, Sophie B.; Gault, Lynden; Nieto, Raquel; Norlin, Veronica; Gallardo, Carmina; Ho, Chak-Sum; Sánchez-Cordón, Pedro J.; et al. (Frontiers in Immunology, 2019)
African swine fever (ASF) is a lethal haemorrhagic disease of domestic pigs for which there is no vaccine. Strains of the virus with reduced virulence can provide protection against related virulent strains of ASFV, but protection is not 100% and there are concerns about the safety profile of such viruses. However, they provide a useful tool for understanding the immune response to ASFV and previous studies using the low virulent isolate OUR T88/3 have shown that CD8+ cells are crucial for protection. In order to develop a vaccine that stimulates an effective anti-ASFV T-cell response we need to know which of the greater than 150 viral proteins are recognised by the cellular immune response. Therefore we used a gamma interferon ELIspot assay to screen for viral proteins recognised by lymphocytes from ASF-immune pigs using peptides corresponding to 133 proteins predicted to be encoded by OUR T88/3. Eighteen antigens that were recognised by ASFV-specific lymphocytes were then incorporated into adenovirus and MVA vectors, which were used in immunisation and challenge experiments in pigs. We present a systematic characterisation of the cellular immune response to this devastating disease and identify proteins capable of inducing ASFV-specific cellular and humoral immune responses in pigs. Pools of viral vectors expressing these genes did not protect animals from severe disease, but did reduce viremia in a proportion of pigs following ASFV challenge.